PWE-268 Recent trends in primary liver cancer in England and Wales. (28th May 2012) - Ladep, N G; Khan, S A; Thillainayagam, A V; Taylor-Robinson, S D; Toledano, M B
Abstract : Introduction: Mortality and incidence rates of Primary Liver Cancer (PLC) have been rising in England and Wales towards the end of the last century. The current trend and ethnic distribution of PLC remain unknown. Methods: We obtained mortality and incidence data for PLC for the whole population of England and Wales for the period 2001–2008. Age-standardised/specific mortality and incidence rates (ASMR/ASpMR and ASIR/ASpIR) of PLC subcategories were calculated. Trends in the rates of hepatocellular carcinoma (HCC) and intrahepatic bile duct tumours (IHBD) were evaluated using a regression method in which a least squares regression line was fitted to the natural logarithm of the rates. About 30% of incidence data for PLC included information on the ethnic origin of the cases and thus we were able to analyse the ethnic distribution of HCC and IHBD for this sub-set over the study period. Results: The ASMR for PLC increased in both sexes: from 3.88 and 2.03 per 100 000 in 2001 to 5.10 and 2.63 per 100 000 in 2008, for males and females respectively. Specifically, there was an increase in the ASMR for both HCC and IHBD of between 4% and 7% per year over the study period. ASIR of HCC increased in men (annual % change: 4%) but not in women. In the ethnic sub-set analysis, more than 79% of HCC and IHBD were registered in men and women of white ethnicity. Black Caribbeans and Africans, as well as Indians were the next most affected ethnic populations. Conclusion: Mortality and incidence rates of PLC continue to increase in England and Wales during 2001–2008, with a modest contribution from immigrant ethnic populations to the increasing trend. Competing interests: None declared.